Coordination Economies, Advertising, and Search Behavior in Retail Markets - Ramey, Garey; Bagwell, Kyle (American Economic Review, 1994)
We introduce a model of the retail firm in which consumers and active firms benefit collectively from coordination of sales at fewer firms. Using this model, we show that ostensibly uninformative advertising plays a key role in bringing about coordination economies, by directing consumer search toward firms that offer the best deals. Optimal consumer search takes the form of a simple rule of thumb that uses observed advertising information to guide search. Both industry concentration and social surplus are higher in the presence of advertising, relative to a no-advertising benchmark. (JEL D83, L15) Many observed advertisements seem to be at odds with rational behavior. In a variety of ads, mostly on TV and radio, multiproduct sellers provide little hard information, choosing instead to impart only vague slogans that are suggestive of good deals. Examples are plentiful: a hardware store